Efficacy of rapid test as an aid in rapid diagnosis of malaria at bed side in an endemic region in comparison to conventional microscopy - Reddy A., Bhaskar; K. N., Deepthi; Eluzai, Zion (International Journal of Contemporary Pediatrics, 2018)
Background: The routine and commonly used test for malaria diagnosis is obtaining thick and thin smears and examining it under microscope. This test required skilled laboratory and skilled staff. Hence rapid diagnostic kits have been developed. Present study attempts to study the efficacy of this optical test in the diagnosis of malaria among children. Objectives of present study was to study efficacy of rapid test in rapid diagnosis of malaria at bed side in an endemic region. Methods: Hospital based cross sectional diagnostic evaluation study was carried out at SVS Medical College, Mahabubnagar, Telangana, India from September 2015 to September 2016. 100 in-patients with fever from pediatric ward belonging to 1-14 years of age were included in the present study after applying the inclusion and exclusion criteria. Results: Maximum children belonged to 1-5 years of age. All patients presented with fever. Splenomegaly, convulsions and pallor was seen in most of the children. Diagnostic accuracy of rapid test was near 100% as it missed only one case of P. falciparum. For vivax malaria there was 100% sensitivity and specificity of the rapid test. For falciparum malaria, it was 97.8% and 100% respectively. Statistically this was significant. Conclusions: Rapid test can be considered as diagnostic test in areas where laboratory facilities are not available. It is cost effective. It takes little time. It can be done anywhere.